A Vector Error Correction Model (VECM) Investigation on Islamic Monetary Policy on Indonesia’s Economic Growth - Nusa Dewa Harsoyo; Fitri Novita; Ahmad Suminto; Galih Aisia (Universitas Al-Qolam Malang, 2026)
Sharia monetary policy is regulated to increase effectiveness in responding to economic developments, particularly in the monetary sector. Indonesia, as a country that implements a dual monetary system, plays a role in balancing the mechanisms of monetary operations and their impact on national economic development. The purpose of this study is to examine the impact of Islamic monetary policy on Indonesia's economic growth from 2020 to 2024. This research uses a quantitative approach with Vector Error Correction Model (VECM) analysis estimation model with the Gross Domestic Product (GDP) as the dependent variable. Sharia Open Market Operation (OPTS), Sharia Indonesian Bank Deposit Facilities (FASBIS) and Sharia Open Market Operation (PUAS) of Islamic monetary policy as independent variables. The results of this study show that the variables that influence GDP are OPTS which is significantly negative and FASBIS which is significantly positive in the long term, while all variables have no effect in the short term. Further research on this topic is recommended to extend the observation period and use other analysis techniques to overcome the limitations of this study in terms of sensitivity to data volume and lag. This study contributes to Islamic monetary economics by showing that Islamic monetary instruments have stronger long-term than short-term effects on economic growth. FASBIS and Sharia Open Market Operations significantly influence GDP, while PUAS has limited impact. Practically, the findings support Bank Indonesia and Islamic banks in optimizing liquidity management and strengthening Islamic monetary policy effectiveness for sustainable economic growth.